2014
DOI: 10.1542/peds.2013-0711
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intoxication Due to an Erroneously Manufactured Dietary Supplement in Seven Children

Abstract: Pediatric cases of vitamin D intoxication (VDI) with dietary supplements have not been previously reported. We report on 7 children with VDI caused by consumption of a fish oil supplement containing an excessively high dose of vitamin D due to a manufacturing error. Seven children aged between 0.7 and 4.2 years were admitted with symptoms of hypercalcemia. Initial median (range) serum concentrations of calcium and 25-hydroxyvitamin D were 16.5 (13.4-18.8) mg/dL and 620 (340-962) ng/mL, respectively. Repeated q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 21 publications
(48 reference statements)
1
36
0
3
Order By: Relevance
“…Fortification of orange juice with vitamin D 2 or D 3 may increase mean serum 25(OH)D with 15–25 nmol/L, with regular consumption . Fortification of dietary supplements carries the risk of vitamin D intoxication, as was recently seen in young children receiving 4000 times as much vitamin D in a fish oil supplement, as was stated on the product …”
Section: Nutrition and Food Fortificationmentioning
confidence: 94%
“…Fortification of orange juice with vitamin D 2 or D 3 may increase mean serum 25(OH)D with 15–25 nmol/L, with regular consumption . Fortification of dietary supplements carries the risk of vitamin D intoxication, as was recently seen in young children receiving 4000 times as much vitamin D in a fish oil supplement, as was stated on the product …”
Section: Nutrition and Food Fortificationmentioning
confidence: 94%
“…Rajakumar et al (2013) described a case study of an infant who had hypervitaminosis D caused by a dosing error in an overthe-counter vitamin D supplement. Cengiz et al reported seven children aged between 0.7 and 4.2 years were admitted with symptoms of hypercalcemia caused by the consumption of a fish oil supplement containing an excessively high dose of vitamin D caused by a manufacturing error (Kara et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kara et al . reported seven paediatric cases admitted with hypercalcaemia and vitamin D intoxication associated with an approximate 4000 times higher vitamin D content than stated within a fish oil supplement. Examples of toxicity associated with inaccurately manufactured and labelled vitamin D supplements is an international problem which is increasingly reported .…”
Section: Safety and Toxicity Of Vitamin Dmentioning
confidence: 97%